The quest for evidence of domestic stock at Blydefontein Rock Shelter - Bousman, C. B.; Mauldin, R.; Zoppi, U.; Higham, T.; Scott, L.; Brink, J. (Southern African Humanities, 2016)
Recent zooarchaeological and aDNA analysis have produced conflicting evidence for the existence of early domestic stock at Blydefontein Rock Shelter. The anatomical analysis identified eight specimens as sheep or sheep/goats, the oldest of which was dated to 2860–2765 BP, while the aDNA results suggest that the oldest identified sheep specimen was either greater kudu or eland. Almost all of the other aDNA identifications conflicted with the anatomical assessments. The faunal and aDNA analyses are presented in separate papers in this journal. This paper provides background information on the site of Blydefontein, and frames the discussion in terms of the reliability and validity of the anatomical and aDNA evidence.